Developing strategy: Do we really need a new paradigm? - H. Oosthuizen (South African Journal of Business Management, 2000)
This article addresses the question of the present-day applicability of the traditional positioning approach to strategy development as being the most appropriate basis for a winning approach. The competence-based alternative is considered to be complementary to the positioning approach. Information was collected by conducting a literature search. The validity of the positioning approach is being disputed because it is claimed that the challenges and opportunities presented by today's deconstructing environmental conditions make any logical and deterministic type of strategy development impossible. However, the findings of this research suggest that the conventional positioning approach to strategy development still constitutes a basic and viable framework under present-day realities. Nevertheless, real-time techniques must be incorporated in order to create a more dynamic and entrepreneurial approach. Thus, it is not believed that a clear need exists to reject the conventional approach and that a cautious view of a possibly new paradigm should be adopted. Current literature suggests a very fragmented field and no clear alternative paradigm seems to emerge. Lessons gleamed from this study suggest that practitioners should guard against 'flitting from one new thing to the next', which are often not that original, and that academics, beyond their search for a new paradigm, should also investigate the empirical relevance of the adapted framework as postulated in this article.
Keywords: 650